Is Thymoglobulin or Rituximab the Cause of This Serum Sickness? A Case Report of Serum Sickness Dilemma and Literature Review - Amarpreet Sandhu; Antonia Harford; Pooja Singh; Eduardo Alas (Case Reports in Medicine)
Serum sickness is an immune-complex-mediated systemic illness that can occur after treatment with monoclonal or polyclonal antibodies such as Rituxan (Rituximab) or antithymocyte globulin (Thymoglobulin), respectively. Since Rituximab is now being used as an adjuvant treatment for acute humoral rejection and its prevalence to cause serum sickness is comparable to Thymoglobulin-associated serum sickness (20% versus 27%), it should be considered a potential cause of serum sickness after rejection treatment. In kidney transplant patients, there are no case reports where patient received both Thymoglobulin and Rituximab before developing serum sickness. We are reporting a patient who developed serum sickness after receiving Thymoglobulin and Rituximab that led us to consider Rituximab as one of the potential causes in this patient’s serum sickness. Since diagnosis of serum sickness is clinical, and Rituximab use has expanded into treatment of glomerulonephritis and acute humoral rejection, it should be considered as a potential offender of serum sickness in these patient populations. There are not any evidence-based guidelines or published clinical trials to help guide therapy for antibody-induced serum sickness; however, we successfully treated our case with three doses of Methylprednisone 500 mg intravenously. Further studies are needed to evaluate Rituximab-associated serum sickness in nephrology population to find effective treatment options.